INTEGRATING TECHNOLOGY FOR SUPPORTING DIFFERENTIATED INSTRUCTION AND ASSESSMENT IN ENGLISH LANGUAGE LEARNER (ELL) CLASSES - Gulsana Selimova (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
This article explores the integration of technology to enhance differentiated instruction and assessment in English Language Learner (ELL) classrooms. It discusses how modern technological tools—such as learning management systems, digital collaboration platforms, and multimedia resources—can be utilized to tailor educational experiences to meet diverse student needs. The article emphasizes the role of technology in facilitating personalized learning, enabling self-paced progress, and providing immediate feedback. By leveraging these tools, educators can create more inclusive environments that support the linguistic and academic development of ELLs.